Chapter Gestione dello stato di criticità organizzativa e gestionale del sistema complesso scuola - Boldi, MARTA (Studies on Adult Learning and Education, 2022)
The evolution of the complex school system, from its origins to school autonomy, explains the reason for the connotation of complexity, which it has acquired over time. The school as organization and as institution therefore is a complex system where leaders and managers become a single person, identified in the School Manager who acts on the basis of continuous improvement. The characteristic features of the managerial function and of the school institution become: governance, leadership, manager, research, communication, organizational culture, and empowerment. The organizational culture understood as sharing assumptions, meanings, values and behaviors, becomes a useful means to achieve the institutional mandate, that is, to ensure student educational success.